2003
DOI: 10.1108/00346650310459527
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phytoestrogens – a role in women’s health

Abstract: Interest into the role of dietary phytoestrogens and their potential effects on women’s health has dramatically increased over the past decade. Phytoestrogens, and in particular isoflavone‐rich soya foods, are now believed to play a role in alleviating symptoms of the menopause, maintaining bone density, reducing blood cholesterol levels, protecting against cancer development. In addition they exhibit potent antioxidant activities. Evidence is now sufficiently strong for both the US FDA and the UK JHCI to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…A high intake of soy isoflavones has been shown to decrease the blood estrogen level in premenopausal women (Kruzer, 2002), which might be related to the alleviation of menstrual distress symptoms. Jefferson (2003) found that foods rich in isoflavones or lignans provide a wide range of vital nutrients and form an integral part of the healthy, low‐fat, high‐fiber diet recommended by dietary experts throughout the world. However, in a study of Japanese women, the soy isoflavone intake was not shown to have any significant relationship with premenstrual and menstrual symptoms (Nagata et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high intake of soy isoflavones has been shown to decrease the blood estrogen level in premenopausal women (Kruzer, 2002), which might be related to the alleviation of menstrual distress symptoms. Jefferson (2003) found that foods rich in isoflavones or lignans provide a wide range of vital nutrients and form an integral part of the healthy, low‐fat, high‐fiber diet recommended by dietary experts throughout the world. However, in a study of Japanese women, the soy isoflavone intake was not shown to have any significant relationship with premenstrual and menstrual symptoms (Nagata et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Jefferson (2003) explained that non‐pharmacological interventions, such as a healthy balanced diet, should be emphasized before resorting to pharmacological treatment as it helps lessen the symptoms of PMS and menopause. The consumption of a healthy balanced diet rich in unrefined carbohydrates and lean protein foods, low in fats (particularly saturated fats), and containing a wide variety of fruits and vegetables should be the goal of every woman.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These isoflavones appear to compete with endogenous oestrogen for receptor binding and act both as oestrogen agonists and antagonists (Kris-Etherton & Hecker, 2002). Scientific studies have shown that women can benefit from dietary manipulation, including increase intakes of phytoestrogens in order to reduce the symptoms experienced during premenopause or menopausal state (Jefferson, 2003). Previous studies (Izumi et al, 2000;Setchell et al, 2001;Zubik & Meydani, 2003) have reported the differences in the absorption rates between glycosylated and aglycone isoflavones.…”
Section: Introductionmentioning
confidence: 97%
“…The protective effects of soy phytoestrogens appear most significant in individuals with initially elevated cholesterol levels; phytoestrogen intake may have less or no effect on individuals with normal cholesterol levels (76,178). On the basis of such findings, the U.S. Food and Drug Administration has approved use of food health claims for intakes of 25 g isoflavone-rich soy protein per day for the reduction of blood cholesterol levels (88). This would equate to approximately 6 mg of genistein per day.…”
Section: Potential Health Beneficial Effects Of Isoflavonoid Phytoestmentioning
confidence: 99%